DOI: 10.18174/472244
|View full text |Cite
|
Sign up to set email alerts
|

How fish larvae swim: from motion to mechanics

Abstract: Table of contents 1 General introduction 2 Biomechanics of swimming in developing larval sh 3 How body torque and Strouhal number change with swimming speed and developmental stage in larval zebra sh 4 Automated reconstruction of three-dimensional sh motion, forces, and torques 5 Reorientation and propulsion in fast-starting zebra sh larvae: an inverse dynamics analysis 6 Fish larvae use similar bending moment patterns across early development and speed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 158 publications
(208 reference statements)
0
3
0
Order By: Relevance
“…Lys278 (273), lysine residue forming a Schiff base (internal aldimine) with the bound PLP in the unliganded enzyme, involved in , -elimination (see Scheme 2 and Section 5.04.2.2.1); Asn209 (202), Tyr240 (233), and Asp237 (230), amino acid residues forming hydrogen bonds with O39 of the pyridine ring and N1 of PLP; Ala127 (120), Thr128 (121), Ser275 (270), Ser277 (272), and Arg286 (281), amino acid residues required for the correct orientation of PLP in the active site, and all of them interact with the oxygens of PLP phosphate moiety (see Scheme 2); Tyr152 (145), mediates the formation of ACC from SAM via a catalytic mechanism involving a quinoid intermediate (according to Li et al 29 ) and stabilizes the pyridine ring of PLP; Glu55 (47), putative ionic interaction between SAM and this residue; Ala54 (46) and Arg412 (407), the -carboxylate group of SAM forms hydrogen bonds with the nitrogen of alanine and the guanidino moiety of arginine; Arg157 (150), O29 and O39 atoms of the sugar of SAM form hydrogen bonds with the guanidine group of arginine; Pro26 (Ser18), Tyr27 (19), Phe28 (20), and Pro153 (144), residues contributing to the hydrophobic pocket for the adenine ring of SAM; Tyr92 (85), probably acts as a platform for the adenine ring of SAM and binds it through a stacking interaction.…”
Section: Inhibitors Of the Catalytical Activity Of Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lys278 (273), lysine residue forming a Schiff base (internal aldimine) with the bound PLP in the unliganded enzyme, involved in , -elimination (see Scheme 2 and Section 5.04.2.2.1); Asn209 (202), Tyr240 (233), and Asp237 (230), amino acid residues forming hydrogen bonds with O39 of the pyridine ring and N1 of PLP; Ala127 (120), Thr128 (121), Ser275 (270), Ser277 (272), and Arg286 (281), amino acid residues required for the correct orientation of PLP in the active site, and all of them interact with the oxygens of PLP phosphate moiety (see Scheme 2); Tyr152 (145), mediates the formation of ACC from SAM via a catalytic mechanism involving a quinoid intermediate (according to Li et al 29 ) and stabilizes the pyridine ring of PLP; Glu55 (47), putative ionic interaction between SAM and this residue; Ala54 (46) and Arg412 (407), the -carboxylate group of SAM forms hydrogen bonds with the nitrogen of alanine and the guanidino moiety of arginine; Arg157 (150), O29 and O39 atoms of the sugar of SAM form hydrogen bonds with the guanidine group of arginine; Pro26 (Ser18), Tyr27 (19), Phe28 (20), and Pro153 (144), residues contributing to the hydrophobic pocket for the adenine ring of SAM; Tyr92 (85), probably acts as a platform for the adenine ring of SAM and binds it through a stacking interaction.…”
Section: Inhibitors Of the Catalytical Activity Of Acsmentioning
confidence: 99%
“…[194][195][196] During drought stress, ABA regulates stomatal closure, whereas increased ethylene production has an inhibitory influence on ABA action. 109 Usually, during plant flooding, ethylene stimulates submergence tolerance and/or underwater shoot growth [201][202][203][204]. 199,200 In contrast, it has been shown that in deepwater rice seedlings ethylene even delays senescence and chlorophyll breakdown upon complete submergence during plant adaptation to low oxygen concentrations.…”
Section: Ethylene and Abiotic Stressesmentioning
confidence: 99%
“…As everybody knows, only the acknowledgements of a PhD thesis are read in detail. This section is, therefore, the excellent place to advertise the research (Voesenek, 2019;Cribellier, 2021). I highlight the experimental work done for this thesis in the following four paragraphs where I thank my students (in sequence of chapters).…”
Section: S Samenvattingmentioning
confidence: 99%